"Music Theatre Now – Global Tendencies And Perspectives", In Music Theatre Now – Programme Of The 2016 Meeting At The Operadagen Rotterdam, 2016, Pp. 10-19. - Roesner, David (Zenodo, 2016)
Music Theatre Now is a competition and subsequent festival organised by the International Theatre Institiute, which celebrates new music theatre from around the Globe. Every three years, practitioners are invited to submitted video documentations, scores and libretti of new works that have been performed at least once. In 2015 an international jury picked 14 from more than 450 submission which they found particularly original, innovative and of high quality. The production came from China, Italy, Russia, Germany, Belgium, Iceland, USA, Mexico, Argentina and Australia. This selection provides, despite all its diversity, a fascinating prism through which to trace some contemporary developments and aesthetic departures, which – particularly when read against the European canon of the operatic tradition – are interesting to look at in more detail. In this festival programme contribution, David Roesner will examine examples of these production and try to tease out some of the share characteristics of what is new and noteworthy about this selection.